Trombosis Arteri Mesenterika - Muhammad Sayuti; Farah Maisyura (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2023)
Mesenteric artery thrombosis is a condition in which there is a narrowing or blockage of one or more branches of the main arteries that supply the small and large intestines called the mesenteric arteries. This condition can lead to mesenteric ischemia and acute mesenteric artery occlusion, which are associated with high morbidity and mortality. The prevalence of patients with mesenteric vein thrombus is not known because many cases are missed because the symptoms are atypical and disappear spontaneously. Early identification and management of non-occlusive mesenteric ischemia (ISNO) reduces mortality by 50-55%, whereas mesenteric vein thrombus has a 30-day mortality rate of 13-15%. The prevalence and incidence of patients with mesenteric ischemia in Indonesia are not known. Mesenteric artery thrombosis can be subdivided into non-occlusive mesenteric artery ischemia and occlusive mesenteric artery ischemia. Patient A 40 year old male came to the emergency room at Cut Meutia Hospital with complaints of abdominal pain for 4 days. Pain comes and goes. Nausea exists. bloody chapters. Before entering the hospital, the patient complained of diarrhea and stopped after taking entrostop.